Focus on artificial frustrated systems - J Cumings; L J Heyderman; C H Marrows; R L Stamps (New Journal of Physics, 2014)
Frustration in physics is the inability of a system to simultaneously satisfy all the competing pairwise interactions within it. The past decade has seen an explosion of activity involving engineering frustration in artificial systems built using nanotechnology. The most common are the artificial spin ices that comprise arrays of nanomagnets with competing magnetostatic interactions. As well as being physical embodiments of idealized statistical mechanical models in which properties can be tuned by design, artificial spin ices can be studied using magnetic microscopy, allowing all the details of the microstates of these systems to be interrogated, both in equilibrium and when perturbed away from it. This ‘focus on’ collection brings together reports on the latest results from leading groups around the globe in this fascinating and fast-moving field.